A rare case of acute non puerperal complete uterine inversion in nulliparous virgin female - Bhangale, Saurabh V.; Kumar, Ashok; Sharma, Mamta; Arora, Naina (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Non-puerperal uterine inversion (NPUI) is extremely rare and accounts for 17% of all uterine inversion cases. A few more than 150 cases have been reported amongst which 10-15 have been reported in nulliparous females and 3-4 have been reported in virgin females from 1914 till date. A 40 years unmarried nulliparous female denying sexual activity presented to our hospital with acute non puerperal complete uterine inversion with something coming out per vaginum of sudden onset while straining at defecation, lower abdominal pain and minimal bleeding per vaginum with history of uterine fibroid and chronic constipation. Diagnosis was confirmed with ultrasonography and examination under anaesthesia after written informed valid consent. After detailed counselling and obtaining written informed valid consent, the patient underwent exploration with a combined abdominal-vaginal approach. Following vaginal myomectomy, the uterus was repositioned using Haultain procedure after a failed attempt of Huntington procedure. Total abdominal hysterectomy with bilateral salpingectomy with vaginal vault suspension was done sparing bilateral ovaries. Diagnosis requires a high index of suspicion and their management is a challenge to gynaecologists due to its rare occurrence, distorted pelvic anatomy and associated pelvic organ injuries during surgery. Good anatomical and clinical knowledge along with surgical skills is of utmost importance for successful outcomes.